Flexion contracture can cause component mismatch in the Prophecy® preoperative patient-specific instrumentation for Evolution® medial-pivot knee system - Hiyama Shuhei; Takahashi Tsuneari; Handa Mikiko; Takeshita Katsushi (SICOT-J, 2024)
Introduction: Patient-specific instrumentation (PSI) systems are used to conduct total knee arthroplasty. PSI reduces operative time, is less invasive and easier to use, and minimizes the risk of errors by providing precise measurements and reducing operating room turnover time. However, a study on the accuracy of Prophecy Evolution PSI (Microport Inc., Arlington, TN, USA) reported that 94% were below the error margin of 1.5 mm and 90% had error margins of 1 mm. This study aimed to evaluate the accuracy of the Prophecy Evolution PSI system in terms of the thickness of “total” bony resection required to achieve adequate extension/flexion gaps and the component match ratio between preoperative planning and actual component size inserted. Methods: Comparisons were made between the sizes of femoral and tibial components planned with PSI and those inserted. The primary outcome was the average preoperative range of motion with and without matched femoral/tibial components. The study further analyzed the proportions of cases in which both the femoral and tibial components matched, neither matched, and only one of the femoral or tibial components matched. Results: The ratio of the same sizes between the PSI planning and those inserted was 50.8% (33 patients) for both the femoral and tibial components. For the femoral component alone, the ratio was 84.6% (55 patients), and for the tibial component, it was 58.4% (38 patients). A receiver-operating characteristic curve analysis indicated that flexion contracture greater than 20° was a significant prognostic factor for the PSI component match group versus the mismatch group. Discussion: Flexion contracture may cause PSI mismatch. Notably, flexion contracture greater than 20° was a significant risk factor for the PSI component match group versus the mismatch group. During preoperative planning for a patient with flexion contracture, surgeons should prepare for the possibility of inserting an undersized tibial component.